THE FUTURE OF LAW: HOW TECHNOLOGY WILL CHANGE LEGAL PROFESSIONS (Anais do Seminário de Atualização de Práticas Docentes, 2022)
THIS SHORT PAPER AIMS TO QUESTION HOW THE TECHNOLOGY REVOLUTION WILL CHANGE THE TRADITIONAL STANDARD OF LAW COURSES ALL OVER THE WORLD AND, OF COURSE, WITH REPERCUSSION IN BRAZIL AND ON THE REALITY OF LEGAL PROFESSIONS. HISTORICALLY, LAW COURSES ARE VERY TRADITIONAL, MOST OF TIMES, USING THE BASE OF STUDY IN STANDARD CODES BASED IN ROMAN GERMANIC LAW. IN ORDER TO UNDERSTAND THE PROFOUND CHANGES, IT IS NECESSARY TO ANALYSE THE RAISE OF TECHNOLOGY IN CONFRONTATION WITH THE CLASSICAL SYSTEM OF LAW. THE FIRST QUESTION IS: ARE LAYERS GOING TO BE REPLACED SOMEDAY, BY ANY ALGORITHMIC MACHINE? MACHINE LEARNING AND DEEP LEARNING ARE GOING TO CHANGE THE HISTORICAL CONCEPT OF LAW? IS IT GOING TO BE POSSIBLE TO CREATE A NEW CLASS OF LAW PROFESSIONALS? ARE LAWYERS GOING TO BE A USELESS CLASS? THOSE QUESTIONS ARE GOING TO BE FACED IN THIS SHORT PAPER. THERE IS GROWING EVIDENCE THAT THESE TRANSFORMATIONS ARE ON THE WAY. WIKIPEDIA, GOOGLE SCHOLAR AND MANY OTHER PLATFORMS ARE REPLACING TRADITIONAL BOOKS AND TRADITIONAL SKILLS. THE USE OF APPS INCREASE MORE EACH DAY. ONLINE COURSES ARE BEING CREATED. THIS PAPER ALSO AIMS TO FIND BETTER SOLUTIONS TO FACE THE CHANGES IN THIS RAPID CHANGE OF PARADIGM, PROPOSING SOME TOOLS TO THE REALITY IN CENTRO UNIVERSITÁRIO DE ANÁPOLIS - UNIEVANGLICA. LAST BUT NOT LEAST, THIS SHORT PAPER WAS ONLY POSSIBLE AFTER THE DISCUSSIONS IN THE SEMINÁRIO DE PRTICAS DOCENTES DA UNIEVANGLICA.
Keywords: TECHNOLOGY, LEGAL EDUCATION, PROFESSION, LAWYER, SOCIETY.